Patient with HR-proficient advanced ovarian cancer achieved a complete response with Cadonilimab combined chemotherapy (PD-1/CTLA-4 bispecific): a case report and literature review - Chenge Zhang; Miao Dai; Jun Yang; Wenfang Tian; Si Huang; Feng Bi; Kai Zheng; Jie Tang (Gynecologic Oncology Reports)
Objectives: For advanced ovarian cancer (OC), particularly OC with HR-deficient, surgery combined with adjuvant chemotherapy and maintenance therapy with PARPi/bevacizumab is the standard effective first-line treatment regimen. However, the clinical benefit of therapy for HR-proficient advanced OC is limited, with no significant increase in the 5-year survival rate. Methods: In this case study, a patient with Stage IVB OC, who tested HR-proficient, but PD-L1 positive, experienced significant tumor shrinkage (>90 %) after undergoing 3 cycles of neoadjuvant chemotherapy using TC (Paclitaxel with Carboplatin) with Cadonilimab (a PD-1/CTLA-4 bispecific antibody) therapy. Results: This resulted in an R0 resection during intermittent debulking surgery. After surgery, while the patient received standard first-line chemotherapy with TC + bevacizumab, the CA125 level failed to normalize. Nonetheless, upon readministration of Cadonilimab, CA125 levels normalized and have been maintained to date. The patient has remained free of recurrence and metastasis for more than 23 months after neoadjuvant therapy, before the data cutoff date, March 10, 2025. Conclusions: This case illustrates that individuals suffering from advanced OC, particularly those with HR-proficient and PD-L1 positive status, may benefit from first-line treatment with Cadonilimab. Identifying the population that may benefit from immune therapy is crucial. The novel PD-1/CTLA-4 bispecific antibody merits further attention for managing advanced epithelial ovarian cancer.Trial registration: NCT05430906, registration date: June 20,2022.